Optical quality and higher order aberrations of refractive extended depth of focus intraocular lenses - Baur, Isabella; Yan, Weijia; Auffarth, Gerd U.; Khoramnia, Ramin; Łabuz, Grzegorz (Journal of refractive surgery, 2023)
PURPOSE: - - To compare the optical quality and higher order aberrations of four different refractive extended depth of focus intraocular lens (EDOF IOL) models (Lentis Comfort [Teleon Surgical BV], MiniWell (SIFI), LuxSmart [Bausch & Lomb], and AcrySof IQ Vivity [Alcon Laboratories, Inc]) and a monofocal IOL (Tecnis ZCB00; Johnson & Johnson Surgical Vision, Inc). - - METHODS: - - An optical metrology instrument (OptiSpheric IOL PRO2; Trioptics GmbH) was used to study image quality metrics of the different IOLs. The modulation transfer function (MTF) was measured at pupil sizes 1 to 5 mm in 1-mm steps. Area under the MTF and simulated visual acuity were calculated for different pupil diameters. Wavefront aberrations were measured with the SHS Ophthalmic device (Optocraft GmbH), which features a Hartmann-Shack sensor. - - RESULTS: - - All EDOF lenses yielded a simulated far visual acuity of 0.00 logMAR (20/20 Snellen) or better. At the 0.20 logMAR visual acuity level, the EDOF IOLs showed an increased depth of focus of at least 0.75 diopters compared to the monofocal IOL. Pupil dependency was more pronounced with the MiniWell, LuxSmart, and Vivity, whereas the Lentis showed a more consistent behavior at different apertures. The wavefront measurement revealed increased central aberrations for the MiniWell, LuxSmart, and Vivity IOL compared to the monofocal control. - - CONCLUSIONS: - - All EDOF IOLs demonstrated increased depth of focus while maintaining good simulated visual acuity at the far focus. Pupil dependency differed between the IOL models. The wavefront analysis revealed the complex design of the different EDOF IOLs with several zones with varying aberrations. - - [J Refract Surg. 2023;39(10):668-674.]